Hydrocarbons from Bio-oils: Performance of the Matrix in FCC Catalysts in the Immediate Catalytic Upgrading of Different Raw Bio-oils - Bertero, Melisa Paola (2017)
Matrices of FCC catalysts with different content of alumina and the compound catalysts prepared with them including Y zeolite were used to upgrade bio-oils from pine wood sawdust and soybean shell. The biomasses were selected according to their different lignin content which results in very different proportions of phenolic compounds (coke precursors) in the respective bio-oils. The bio-oils were produced by fast pyrolysis and the vapours were immediately upgraded over a fixed bed of catalyst at 550 °C using a mass catalyst/bio-oil relationship of 3.5. In terms of hydrocarbon yield, the matrices were more effective in deoxygenating pine wood sawdust bio-oil and the compound catalysts in deoxygenating soybean shell bio-oil. These differences can be the consequence of the different compositions of the bio-oils which, in the case of pine wood sawdust, includes a significant concentration of phenolic ethers which form coke on the matrix and the external surface of the zeolite, thus preventing lighter compounds from accessing the micropore system of the compound catalysts. Pine sawdust bio-oil produced more coke than soybean shell bio-oil; in the case of compound catalysts, coke deposited preferentially on the catalyst matrix, thus decreasing its mesopore specific surface area up to 65 %.